Achieving sustainability goals through water efficiency in residential building - Alaa Badr Eldeen Mohamed Hussain; Hesham Sameh Hussien Sameh (Cairo : Alaa Badr Eldeen Mohamed Hussain, 2018)
The Research highlighted the improvement of water use efficiency as the best solution for exploiting available water resources in Egypt during water conservation techniques, which in turn reduces energy consumption as it relates to water consumption. This is done through the use of high efficient products in using water and studying how to apply them in buildings. Or buildings under construction. This study led to knowledge of the water saving rate after application. Since the world is currently pursuing the principle of sustainability and green architecture and the principle of recycling and reuse, it realized that some of the objectives of sustainability is to improve the efficiency of water use by recycling rain water, gray water and black water and reuse for purposes that do not require potable water such as agriculture, Cars and others. After comparing traditional buildings with buildings with water recycling systems applied and applying modern technologies that increase water use efficiency, these systems provide 80% water
Thesis (M.Sc.) - Cairo University - Faculty of Engineering - Department of Architectural Engineering
Issued also as CD
Keywords: Grey water; Water consumption; Water efficiency